Optic nerve double inversion recovery hypersignal in patients with clinically isolated syndrome is associated with asymptomatic gadolinium-enhanced lesion. (December 2019) - London, Frédéric; Zéphir, Hélène; Hadhoum, Nawal; Lannoy, Julien; Vermersch, Patrick; Pruvo, Jean-Pierre; Hodel, Jérôme; Leclerc, Xavier; Outteryck, Olivier
Background: Optic nerve involvement is not considered in dissemination in space (DIS) or time (DIT) of multiple sclerosis (MS) lesions. Objectives: To evaluate frequency of optic nerve involvement using three-dimensional (3D)-double inversion recovery (DIR) sequence in clinically isolated syndrome (CIS) and to measure its relationship with DIS and DIT (2010 and 2017 McDonald criteria). Methods: From November 2013 to August 2016, 57 CIS patients underwent 3T-magnetic resonance imaging (3T-MRI) including 3D-DIR sequence and optical coherence tomography (OCT) at 3 months after CIS. We assessed signal abnormalities of the optic nerves on DIR sequence and collected data for DIS and DIT criteria according to 2010 and 2017 McDonald criteria. Results: Among the 57 recruited patients, the presence of ⩾1 DIR hypersignal in optic nerve was observed in 36 (63%; 48 optic nerves) including asymptomatic hypersignal in 22 (38.5%; 25 optic nerves). Optic nerve involvement was significantly associated with DIT ( p = 0.006) and MS according to 2010 criteria ( p = 0.01) but was not significantly associated with presence of DIS criteria according to 2010 and 2017 McDonald criteria. We identified a significant ( p < 0.001) temporal peripapillary retinal nerve fiber layer thinning on eyes with optic nerve involvement versus healthy controls. Conclusions: Optic nerve involvement is very frequent at the earliest clinical stage of MS. It is associated with the presence of asymptomatic gadolinium-enhancement and retinal axonal loss and may reflect the inflammatory disease activity level.